Genetic divergence studies for yield and yield attributes in bitter gourd (Momordica Charantia L.) (Bangladesh Journal of Botany, 2025)
The present experiment was conducted during Rabi season of 2017-18 to study genetic diversity for quantitative and qualitative traits in bitter gourd and twenty seven genotypes were grouped into eight clusters which indicate the presence of diversity for different traits. The cluster II had the highest number containing 12 genotypes followed by cluster I containing seven genotypes. The maximum intra-cluster distance (96.27) was recorded within cluster VIII and the maximum inter-cluster distance (1028.37) was between cluster VIII and I indicating the existence of wide genetic variability. The cluster VIII (329.15 cm) registered maximum vine length. The genotypes included in clusters VI were with high number of primary branches per vine, cluster III took less number of days (45.40) to first female flowering, cluster IV took less number of days(43.51) to first fruit harvest and cluster I took more number of days(143.19) to last harvest. The cluster VI registered high number (20.70) of fruits per vine and high fruit length (19.31 cm). The genotypes included in clusters VIII had maximum average fruit weight (41.90 g). Less fruit fly infestation (21.17 %) and high number (20.20) of seeds per fruit were observed in cluster VI.  The clusters with genotypes VIII registered high 100 seed weight (19.49 g) and total fruit yield per vine (6.58 kg) which can be utilised in breeding programme for enhancing their respective characters. Based on cluster mean analysis these genotypes can be used in crop improvement programme in bitter gourd for above-mentioned characters.Bangladesh J. Bot. 54(4): 1061-1067, 2025 (December)